A Test of the Relationships between Host and Home National Involvements and the Preferences for Intercultural Conflict Management Styles. Issue 4 (4th July 2017) - Oommen, Deepa
Abstract: This study focused on the relationships between host national (host interpersonal communication) and home national (ethnic interpersonal communication) involvements and preferences for conflict management styles in the context of a conflict with a member of the host culture. Two hypotheses that examined the relationships between these variables and the preferences for the integrating, the compromising, the avoiding, the obliging and the dominating styles were proposed. Survey data from two hundred and sixty-nine, international and exchange, students were analyzed. The results revealed that the level of host national involvement positively predicted the preferences for the integrating and the obliging styles, and the level of home national involvement positively predicted the preference for the avoiding style. These findings suggest the need to consider contextual influences in understanding the complexities that underlie intercultural communication and adaptation.